Report on the Current Inventory of the Toolbox for Plant Cell Wall Analysis: Proteinaceous and Small Molecular Probes - Rydahl, Maja G.; Hansen, Aleksander R.; Kračun, Stjepan K.; Mravec, Jozef (Frontiers in Plant Science, 2018)
Plant cell walls are highly complex structures composed of diverse classes of polysaccharides, proteoglycans, and polyphenolics, which have numerous roles throughout the life of a plant. Significant research efforts aim to understand the biology of this cellular organelle and to facilitate cell-wall-based industrial applications. To accomplish this, researchers need to be provided with a variety of sensitive and specific detection methods for separate cell wall components, and their various molecular characteristics in vitro as well as in situ. Cell wall component-directed molecular detection probes (in short: cell wall probes, CWPs) are an essential asset to the plant glycobiology toolbox. To date, a relatively large set of CWPs has been produced – mainly consisting of monoclonal antibodies, carbohydrate-binding modules, synthetic antibodies produced by phage display, and small molecular probes. In this review, we summarize the state-of-the-art knowledge about these CWPs; their classification and their advantages and disadvantages in different applications. In particular, we elaborate on the recent advances in non-conventional approaches to the generation of novel CWPs, and identify the remaining gaps in terms of target recognition. This report also highlights the addition of new ‘compartments’ to the probing toolbox, which is filled with novel chemical biology tools, such as metabolic labelling reagents and oligosaccharide conjugates. In the end, we also forecast future developments in this dynamic field.